An Approach for Multi-Artifact Testing Through an Ontological Perspective for Behavior-Driven Development - Thiago Rocha Silva; Jean-Luc Hak; Marco Winckler (Complex Systems Informatics and Modeling Quarterly)
In a user-centered development process, artifacts evolve in iterative cycles until they meet users’ requirements and then become the final product. Every cycle gives the opportunity to revise the design and to introduce new requirements which might affect the specification of artifacts that have been set in former development phases. Testing the consistency of multiple artifacts used to develop interactive systems every time that new requirements are introduced is a cumbersome activity, especially if it is done manually. This paper proposes an approach based on Behavior-Driven Development (BDD) to support the automated assessment of artifacts along the development process of interactive systems. The paper uses an ontology for specifying tests that can run over multiple artifacts sharing similar concepts. A case study testing Task Models, Prototypes, and Final User Interfaces is presented to demonstrate the feasibility of this approach from the early phases of the design process, providing a continuous quality assurance of requirements, and helping clients and development teams to identify potential problems and inconsistencies before commitments with software implementation are made.